Outbreak of Escherichia coli O157 in a nursery: lessons for prevention. Issue 1 (1st July 1999) - Al-Jader, L; Salmon, R L; Walker, A M; Williams, H M; Willshaw, G A; Cheasty, T
Abstract : OBJECTIVES: To identify risk factors for transmission of verocytotoxin producing Escherichia coli O157 (VTECO157) and means of prevention. STUDY DESIGN: Outbreak investigation: retrospective cohort study. SETTING: A nursery (child care centre) in North Wales. SUBJECTS: Children attending (n = 104). METHODS: Faeces were examined using sorbitol MacConkey agar (SMAC), with cefixime, tellurite, and rhamnose; enrichment in modified tryptone soya broth; and immunomagnetic separation. Symptoms and exposure data were obtained from questionnaires to parents/guardians and children's toiletting and feeding records kept at the nursery. MAIN OUTCOME MEASURE: A "case" was defined as a child with verocytotoxin producing E coli O157 isolated from faeces, or a history of haemolytic uraemic syndrome (HUS) and antibodies to E coli O157 lipopolysaccharide, during the period 10 August to 30 September 1995. RESULTS: The attack rate was 31 in 104. Two children developed HUS. There were higher attack rates among girls and friends who played together. Cases were more likely to attend the nursery more frequently. The mean number of recorded bowel motions/child/half day was 0.51 in cases and 0.21 in well children. Child to staff ratios were high preceding and during the outbreak. CONCLUSIONS: A sick child is the most plausible source of infection with subsequent person to person transmission. The record of children's toiletting discriminated between cases and well children and might have allowed earlier detection of the outbreak. This simple record could be considered by other child care facilities as a means of giving early warning of problems with infectious intestinal diseases.